Analysis of Figurative Language in Hikayat Aceh Written by Muda Balia - Puteri Khalida Zia; Zulfadli A. Aziz; Burhansyah Burhansyah (Universitas Syiah Kuala, 2019)
This research entitled “Analysis figurative language in Hikayat Aceh written by Muda Balia” aims at identifying and analyzing the types of figurative language that has been used in Hikayat Aceh written by Muda Balia. In analyzing the data, the researcher used a descriptive analysis. The data were analyzed based on figurative language theory proposed by Prof. Dr. Nyoman Kutha Ratna, there are 21 figurative languages. The result of this research shows that Muda Balia uses the figurative language to convey and clarify his purpose through his Hikayat. There are 10 types of figurative language found in Hikayat Aceh, they are apheresis, allonym, anti-climax, hyperbole, personification, metaphor, synecdoche, euphemism, simile and antithesis. It was found that apheresis is dominated the whole use of figurative language in Hikayat Aceh.